Optimisation of Quality Evaluation of Biscuits Formulated by Linear Programming - K. Murali Naik, A. Rama Rao, P. Vijetha, Sukthija M. P. (International Journal of Advanced Science and Technology, 2020)
Three soy and jowar based food formulations for children, adult male and female were formulated by using a linear programming model to reduce the total cost of production so as to meet the requirements of proteins, calories and also crude fiber demands. The physical properties of the biscuits have been studied and showed that, with increase in amount of soy bean the diameter and thickness of biscuit is decreased as spread ratio is increased. Texture analysis were also done to measure the hardness of the biscuit result showed the increase in hardness of biscuit with increase in soy. Proximate analysis had given desirable nutrition values to meet the daily requirement of the children, adult male and adult female for protein, calories, fiber and calcium. Sensory evaluation revealed that the prepared samples are of having almost similar acceptability when compared with the locally made biscuits